Contemporary evolution of Tibetan-style dwellings under urbanization: a case study of the Shannan city - Feng Xu; Yunfeng Bai; Baohua Wen; Wenxi Xie; Lijuan Huang; Yangnan Ou; Xihong Luo; Qingxin Yang (Journal of Asian Architecture and Building Engineering)
Tibetan-style dwellings form a significant part of China’s residential heritage, reflecting distinct plateau characteristics and a rich Tibetan cultural history. With the rapid advancement of urbanization, traditional Tibetan-style dwellings have evolved spontaneously to accommodate modern lifestyles. This study focuses on Tibetan-style dwellings in the urban villages of Shannan City, Tibet Autonomous Region, as research samples. Through fieldwork and on-site measurements, the study documents the evolution of these dwellings, identifying the spontaneous changes in the context of urban development. It explores the mechanisms by which urbanization influences the evolution of Tibetan-style dwellings and proposes strategies for their scientific development. The findings reveal that local Tibetan-style dwellings have undergone significant changes in various aspects, including house forms, overall layout, spatial functions, and structural decorations over time. The driving factors behind these changes include economic conditions, industrial and population structures, education levels, the materials market, construction technology, and housing needs. Based on the characteristics and mechanisms of the evolution of Tibetan-style dwellings, the study offers recommendations for their modernization, providing valuable insights for their sustainable development.